Characterization and classification of whole-grain rice based on rapid visco analyzer (RVA) pasting profile - B., Shafie; Cheng, S. C.; Lee, Huei Hong; Yiu, Pang Hung (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Classification of whole grain rice using only amylose content is not practical to predict starch viscosity for end product recommendation. This study aims to characterize and categorize whole-grain rice based on pasting profile of Rapid Visco Analyzer (RVA). The rice cultivars showed a wide range of peak viscosity (89.98 to 280.95 RVU), hold viscosity (59.97 to 211.56 RVU), breakdown viscosity (-0.33 to 130.67 RVU), final viscosity (111.25 to 390.75 RVU), setback viscosity (-44.47 to 205.67 RVU) and pasting temperature (74.17 - 91.15oC). Stability ratio and final viscosity explained 68.8% of total variance in the RVA profiles. The rice cultivars could be grouped into high (> 0.95), medium (0.65-0.95) and low (< 0.65) stability ratio, followed by high (> 300 RVU), medium (140 - 250 RVU) and low (< 140 RVU) final viscosity. The classification could serve as a basis for effective rice selection according to functional properties of whole grain rice.